Extraction of Protein from Yellowfin Tuna (Thunnus albacares) Waste by Enzymatic Hydrolysis and its Characterization - Parvathy, U.; Zynudheen, A. A.; Panda, S. K.; Jeyakumari, A.; Anandan, R. (Fishery Technology, 2016)
The focus of this investigation was to utilize the protein present in tuna waste by enzyme hydrolysis and characterization of protein hydrolysate (TPH). Yellowfin tuna waste was used to prepare the hydrolysate using 0.5% (w/w) bromelain enzyme. It was characterized for nutritional, functional and antioxidant properties. The protein content in the derived protein hydrolysate was 95.3 Â± 3.1%. The foaming capacity as well as foam stability was maximum at pH 6.0 and the property decreased when pH deviated from neutral. Emulsifying properties viz., emulsifying activity index as well as emulsion stability index was least at 4.0 pH. DPPH radical scavenging activity of TPH revealed an IC50 value of 4.06 mg ml-1.